Repeated nondiagnostic result of thyroid fine-needle aspiration biopsy - Klaudia Ziemiańska; Janusz Kopczyński; Aldona Kowalska (Contemporary Oncology, 2017)
Aim of the study: Fine-needle aspiration biopsy (FNAB) is the most accurate and cost-effective method to evaluate the risk of malignancy of thyroid nodules, but approximately 1–24% of FNABs generate a nondiagnostic result (ND-FNAB). The aim of this study was to determine the predictive factors of a repeated nondiagnostic result of FNAB. Material and methods : A total of 4018 FNABs performed in a territorial referral centre were analysed, of which 288 (7.17%) were nondiagnostic. Medical records were available for 245 biopsies performed in 228 patients. The retrospective analysis of factors that may influence a repeat ND-FNAB, including demographic, clinical and ultrasound characteristics, was performed. Results : A repeat FNAB was performed in 159 nodules giving a diagnostic result in 79.2% of cases. The time between the biopsies ranged from 1 to 611 days (mean 154.4, median 119). The timing of a repeat FNAB did not significantly alter the diagnostic output (p = 0.29). In the univariate analysis, significant predictors of a repeat ND-FNAB were older patient age (p = 0.02), L-thyroxine supplementation (p = 0.05), and a history of 131 I therapy (p < 0.0001). In the multivariate analysis, only a history of 131 I therapy was a statistically significant risk factor for a repeat ND-FNAB (p = 0.002). Conclusions : Patients with a history of 131 I therapy and ND-FNAB should undergo periodic ultrasonographic assessment rather than a repeat biopsy. The interval between repeated FNABs recommended by guidelines does not affect the diagnostic output.